Multi-material hot-melt inkjet 3D printing: towards complex and personalised dosage form - Lion, Anna (2021)
Three-dimensional printing includes a wide variety of manufacturing techniques, which are based on the digitally controlled deposition of materials (layer-by-layer) to create freeform 3D geometries. 3D printing with single-materials is a well-established technology that has found application across many different fields from engineering to medicine and pharmacy by enabling the production of complex and high quality prototypes and devices that were previously either difficult to manufacture expensive or time consuming.